KAJIAN HASIL TANGKAPAN NELAYAN GILL NET DI PANGKALAN PENDARATAN IKAN (PPI) TANJUNG LIMAU KOTA BONTANG - Nurul Hikmah; Said Abdusysyahid; Gusti Haqiqiansyah (2339-1324, 2017)
The purpose of this research is to : know the type of fish catches and the volume of fish production that landed at the landing fish (PPI) Tanjung Limau, Bontang; to know the revenue and profit fishermen gill net in the landing fish (PPI) Tanjung Limau, Bontang; to know the return on investment of fishermen gill net in the landing fish (PPI) Tanjung Limau, Bontang. Collection the data held on May to June 2016 in Fish Landing Base (PPI) Tanjung Limau, Bontang. The data collection by means of observation immediately and are based on interviews with 15 of the respondents using a list of question. The methode is the Example of using techniquesn Random Sampling where the samples at random, the catch and the volume of fish production that landed at the landing fish (PPI) Tanjung Limau, Bontang City. Using analysis of descriptive, while income and profits for fishermen gill net in the analysis by the application of the analysis ofprofit the cost of R/C Ratio and Paybak Periode.The results of research showed that the alleged income the fishermen is Rp. 5.628.841/respondents. Futhermore, Revenue Cost Ratio (R/C Ration) of the catch of fishermen Gill Net benefited becous thevalue of RCR = 1.9 > 1 a time and return on investment is 7,1 month means that the intial investment that was instilled will be back in time of 7,1 month.